Economic behaviours among non-human primates. (1st March 2021) - Bourgeois-Gironde, Sacha; Addessi, Elsa; Boraud, Thomas
Abstract : Do we have any valid reasons to affirm that non-human primates display economic behaviour in a sufficiently rich and precise sense of the phrase? To address this question, we have to develop a set of criteria to assess the vast array of experimental studies and field observations on individual cognitive and behavioural competences as well as the collective organization of non-human primates. We review a sample of these studies and assess how they answer to the following four main challenges. (i) Do we see any economic organization or institutions emerge among groups of non-human primates? (ii) Are the cognitive abilities, and often biases, that have been evidenced as underlying typical economic decision-making among humans, also present among non-human primates? (iii) Can we draw positive lessons from performance comparisons among primate species, humans and non-humans but also across non-human primate species, as elicited by canonical game-theoretical experimental paradigms, especially as far as economic cooperation and coordination are concerned? And (iv) in which way should we improve models and paradigms to obtain more ecological data and conclusions? Articles discussed in this paper most often bring about positive answers and promising perspectives to support the existence and prevalence of economic behaviours among non-human primates. This article is part of the theme issue 'Existence and prevalence of economic behaviours among non-human primates'.